Ipilimumab, a Promising Immunotherapy with Increased Overall Survival in Metastatic Melanoma? - Gérald E. Piérard; François Aubin; Philippe Humbert (Dermatology Research and Practice)
Malignant melanoma (MM) is one of the most aggressive skin cancer. The therapeutic options remain limited for advanced MM, and those directed to the neoplastic cells have not brought major survival advantage so far. Immunotherapy is another targeted option. Ipilimumab, a monoclonal antibody directed to CTLA-4 present on cytotoxic T cells boosts immunity, particularly its anti-MM activity. Under treatment, the overall survival of patients with MM metastases is moderately but significantly increased. The immuno-related adverse effects may be severe and life threatening.